Menganalisis Perbandingan E-commerce dan UMKM pada Mahasiswa Sekolah Vokasi IPB University - Zahra, Afnan; Bintang, Denty Nirwana; Barus, Irma Rasita Gloria; Fami, Amata (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The rapidly developing digital economic context, including Indonesia, has changed the global business landscape. Understanding the preferences and involvement of the younger generation, especially students, is crucial. This research aims to compare the preferences and involvement of IPB University Vocational School students in the use of E-commerce and involvement in Micro, Small, and Medium Enterprises (MSMEs). This research uses a quantitative method, with a survey conducted using a questionnaire of 32 students to obtain students' perspectives and experiences regarding comparing e-commerce and MSMEs. The data collected was then analyzed to identify significant differences between students who were more likely to use E-commerce platforms for online shopping compared to those who preferred shopping in MSMEs. This research also digs deeper into the factors that influence student preferences and ways to optimize their potential in encouraging inclusive and sustainable economic growth